2004
DOI: 10.2320/matertrans.45.1077
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of a Ti-Nb-Al Shape Memory Alloy

Abstract: Ni-free Ti-base shape memory alloys (SMA) have been systematically developed by our group for biomedical applications in order to replace Ti-Ni SMAs which posses the possibility of Ni-hypersensitivity. In this study, superelastic behavior of solution-treated Ti-24 mol%Nb-3 mol%Al alloy was investigated by means of tensile tests at room temperature (RT) as well as microstructural observation. The alloy was fabricated by Ar arc-melting followed by a homogenization at 1273 K and then cold-rolled with the reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
107
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 187 publications
(115 citation statements)
references
References 9 publications
5
107
0
3
Order By: Relevance
“…19,20 Nickel-free titanium-based SMAs composed of nontoxic elements have been systematically investigated. 21 Titanium-niobium-aluminum (Ti-Nb-Al) alloy, 21 which has the best mechanical performance among these nickel-free shape memory and superelastic alloys, was recently developed as a result of advances in processing technology. The aim of this study was to examine the mechanical properties and the usefulness of Ti-Nb-Al wire in orthodontic tooth movement as compared with Ni-Ti wire.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Nickel-free titanium-based SMAs composed of nontoxic elements have been systematically investigated. 21 Titanium-niobium-aluminum (Ti-Nb-Al) alloy, 21 which has the best mechanical performance among these nickel-free shape memory and superelastic alloys, was recently developed as a result of advances in processing technology. The aim of this study was to examine the mechanical properties and the usefulness of Ti-Nb-Al wire in orthodontic tooth movement as compared with Ni-Ti wire.…”
Section: Introductionmentioning
confidence: 99%
“…In Ti-Nb binary alloys, superelastic behavior was observed at room temperature when the Nb content is 26$27 at% Nb. 1) The superelasticity has been also reported in ternary alloys such as Ti-Nb-Sn, 2) Ti-Nb-Zr, 3) Ti-Nb-Ta, 4) Ti-Nb-Al, 5) Ti-Nb-Pt 6) and Ti-Nb-O. 7) In addition, it has been also reported that the superelasticity was observed in Ti-Mobased alloys such as Ti-Mo-Sn, 8) Ti-Mo-Sc 9) and Ti-MoGa.…”
Section: Introductionmentioning
confidence: 90%
“…This has led to the development of Ni-free -Ti base shape memory alloys which consist of only non-toxic elements. [1][2][3][4][5][6][7][8][9][10][11][12] In -Ti alloys, superelasticity is associated with a stress induced martensitic transformation from the phase (bcc) to 00 martensite phase (orthorhombic) by loading and its reverse transformation by unloading. The control of the martensitic transformation temperatures by the adjustment of the amount of -stabilizer elements such as Nb, Mo and Ta is necessary to obtain the superelasticity in Ti-base alloys.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Young's modulus of Ti-Nb alloys, which is quenched above the β transus temperature, depends on the niobium (Nb) content [14,15]. Depending on the chemical composition, Ti alloys exhibit some intermediate phases, such as non-equilibrium hcp-α 0 , orthorhombic-α 00 , and hexagonal-or trigonal-ω phases between the equilibrium α and β phases [17]. As a function of the chemical composition, the Young's modulus of Ti-Nb alloys shows local maximum at the chemical composition in which the ω phase is formed by quenching (Ti-30Nb).…”
Section: Low Young's Modulusmentioning
confidence: 99%
“…ϕ is angles between longitudinal and rolling directions in specimen, and M s is α 00 martensitic transformation temperature [11] temperatures just below these temperatures [16]. Newly developed β-type Ti alloys such as Ti-Nb-Ta-Zr [7,8], Ti-Nb-Sn [16,9,15], Ti-Nb-Al [11,17], Ti-Nb-Ta [18], and Ti-Nb-Zr-Sn [10] alloys are considered to satisfy the abovementioned requirements for obtaining low Young's modulus of the order of 40-60 GPa, which is close to that of the bone (10-30 GPa) [19]. However, the mechanical reliability of these β-type Ti alloys with low Young's modulus is typically lesser than that of a common (α + β)-type Ti-6Al-4V ELI alloy.…”
Section: Low Young's Modulusmentioning
confidence: 99%